2020
DOI: 10.14254/2071-8330.2020/13-1/3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of regional trade agreements: Global evidence based on gravity models

Abstract: There has been a continuous increase in the number of regional trade agreements (RTAs) worldwide during the previous decades. However, the analysis of determinants of regional trade agreements is somehow neglected in empirical literature. This paper aims to analyse the determinants of regional trade agreements by using gravity variables on a global sample. The results suggest that colonial variables are ambiguously related to RTAs, thereby making it hard to exactly define the role of colonial relations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The low competitiveness of Indonesian cocoa beans in the global market due to the enactment of cocoa export duties and the low quality of non-fermented cocoa bean exports caused asymmetrical interactions between the domestic Indonesian and world cocoa markets (Witjaksono and Asmin 2016;Hasibuan and Sayekti 2018). Meanwhile, the establishment of a regional trade treaty among the cocoa producers reduced competition in the world cocoa market (Jambor, Gal, and Torok 2020). Generally, our findings also demonstrate the sensitivity of Indonesian net export, macroeconomic policies, and market flux to the changes in foreign currency of the USD.…”
Section: The Long-run Impacts Of European Cocoa Price Inflation Global Oil Prices and Exchange Rate On The Indonesian Cocoa Pricesupporting
confidence: 66%
“…The low competitiveness of Indonesian cocoa beans in the global market due to the enactment of cocoa export duties and the low quality of non-fermented cocoa bean exports caused asymmetrical interactions between the domestic Indonesian and world cocoa markets (Witjaksono and Asmin 2016;Hasibuan and Sayekti 2018). Meanwhile, the establishment of a regional trade treaty among the cocoa producers reduced competition in the world cocoa market (Jambor, Gal, and Torok 2020). Generally, our findings also demonstrate the sensitivity of Indonesian net export, macroeconomic policies, and market flux to the changes in foreign currency of the USD.…”
Section: The Long-run Impacts Of European Cocoa Price Inflation Global Oil Prices and Exchange Rate On The Indonesian Cocoa Pricesupporting
confidence: 66%
“…It was found that, according to factors contributing to the increase in RTAs analysis, the usage of common languages and the influence of distances play an essential role. On the other side, geographical indication does not play a significant role in regional trade agreements (Jámbor et al 2020). Moreover, it has been proven that countries trade with each other based on the size of their GDP, population, cultural affinity, institutional support and physical proximity (Jindřichovská 2020).…”
Section: Literature Analysismentioning
confidence: 99%
“…The fundamental weakness of terminology is that the terms need to meet with two opposite requirements: they need to be fixed, but they need to remain flexible in order to cope with technological and other changes (Vasa, 2010;Ercsey-Ravasz et al, 2012;Vladár, 2013;Dziubanovska, 2019;Vajda, 2020). Theoretical research focusing on regional trade systems are fundamental in this regard (Jámbor et al, 2020)…”
Section: International Trade Terminologymentioning
confidence: 99%